The key players of dysbiosis in Noma disease; A systematic review of etiological studies - Ifeanyi Uzochukwu; David Moyes; Gordon Proctor; Mark Ide (Frontiers Media S.A., 2023)
Noma is a rapidly progressing periodontal disease with up to 90% mortality in developing countries. Poor, immunocompromised and severely malnourished children (2 to 6 years old) are mostly affected by Noma. Prevention and effective management of Noma is hindered by the lack of sufficient cohesive studies on the microbial etiology of the disease. Research efforts have not provided a comprehensive unified story of the disease. Bridging the gap between existing studies gives an insight on the disease pathogenesis. This current systematic review of etiological studies focuses on the key players of dysbiosis in Noma disease. This review was performed in accordance with the Preferred Reporting Items for Systemic review and Meta-Analyses (PRISMA) statement. Web of Science, MEDLINE via PubMed, Cochrane Library, Scopus, and Science Direct were searched electronically for clinical trials which applied culture dependent or molecular techniques to identify oral microbiota from Noma patients. Trials which involved periodontal diseases except Noma were excluded. After screening 275 articles, 153 full-texts articles were assessed for eligibility of which eight full text articles were selected for data extraction and analysis. The results show that 308 samples from 169 Noma participants (6 months to 15 years old) have been used in clinical trials. There was some variance in the microbiome identified due to the use of 3 different types of samples (crevicular fluid, subgingival plaque, and swabbed pus) and the ambiguity of the stage or advancement of Noma in the studies. Other limitations of the studies included in this review were: the absence of age-matched controls in some studies; the constraints of colony morphology as a tool in distinguishing between virulent fusobacterium genus at the species level; the difficulty in culturing spirochaetes in the laboratory; the choice of primers in DNA amplification; and the selection of probe sets in gene sequencing. This systematic review highlights spirochaetes and P. intermedia as putative trigger organisms in Noma dysbiosis, shows that F. nucleatum promotes biofilms formation in late stages of the disease and suggests that future studies should be longitudinal, with high throughput genome sequencing techniques used with gingival plaque samples from early stages of Noma.